A porous cross-linked gel polymer electrolyte separator for lithium-ion batteries prepared by using zinc oxide nanoparticle as a foaming agent and filler. (1st December 2018) - Gu, Luming; Zhang, Mingzu; He, Jinlin; Ni, Peihong
Abstract: In this work, a new porous cross-linked membrane is prepared and used as the separator for rechargeable lithium-ion batteries. The inorganic zinc oxide nanoparticle (nano-ZnO) was added as a pore-forming agent and filler to the preparation process of membranes composed of poly(vinylidene fluoride- co -hexafluoropropylene) (PVdF-HFP) and a cross-linked polymer by the copolymerization from poly(ethylene glycol methyl ether methacrylate) (PEGMEMA), methyl methacrylate (MMA) and octavinyl-T8-silsesquioxane (OVPOSS). The prepared membrane was firstly swollen by propylene carbonate (PC) and nano-ZnO was then eluted by hydrochloric acid to form the microporous structure. The effects of particle size and additive amount of nano-ZnO on the mechanical and electrochemical properties of microporous membranes were studied. SEM analysis showed that 30 nm nano-ZnO was the most suitable diameter for forming microporous structure. It is generally considered that the ionic conductivity is inversely correlated with the mechanical strength of separator. In our research, we have found that 18% addition of nano-ZnO was the most appropriate amount for the preparation of a microporous membrane (CRZ18) with an ionic conductivity of 1.4 mS cm −1 and a tensile strength of 10.7 MPa. Meanwhile, the LiFePO4 /Li half-cell assembled with the CRZ18 membrane as a separator exhibited the best C-rate capacity and cycle charge-discharge performance, indicating that the CRZ18 membrane would be a kind of promising separator for the high-performance lithium-ion batteries. Highlights: A new porous membrane is prepared using nano-ZnO as the additive and pore-forming agent. The additive shows favorable pore-forming properties and the resultant membrane maintains considerable mechanical strength. Good thermal stability and mechanical strength contribute to higher battery safety. Half-cell assembled with membrane shows stable cycling and good rate performance.